(untitled) (International Journal of Food and Nutritional Sciences, 2023)
India being a developing country, the issue of food security and malnutrition has always been bothering the nutritionists as well as the government of the country. Triple burden of malnutrition nowadays is a major cause of concern, where iron deficiency anemia is leading the board. 64% of pregnant women in Ropar district were found to be anemic, the reason for which varied from age to number of pregnancies and poor dietary intakes. Although, to eradicate this high prevalence of anemia the Government of India have made many interventions as free iron and folic acid supplementations and free or cheap antenatal health checkups in government hospitals and dispensaries, yet the prevalence is high enough. The most convincing cause of this is lack of education and awareness among the population. Second factor might be the inefficiency of these schemes at ground level. Moreover, the consumption of iron and folic acid tablets during pregnancy alone would not be enough to cope up with the high demands of iron during pregnancy, it is important to maintain the nutritional stores before conceiving. So, the diet and nutritional status from menarche to the time a woman is planning to conceive affects greatly the outcomes of pregnancy